Introduction to Trends and Patterens of Fdi Inflows In India: The Impact of FDI on Economic Growth and Integration in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
One of  the  most prominent  and  striking feature  of  today’s globalised  world  is  theexponential growth of FDI in both developed and developing countries. In thelast two decades  the  pace of  FDI  flows are  rising  faster than  almost  all other  indicators  of economic activity worldwide. Developingcountries, in particular, considered FDI as the safest  type of  external  finance as  it  not only  supplement  domestic savings,  foreign reserves  but promotes  growth  even more  through  spillovers of  technology,  skills, increased innovative capacity, anddomestic competition. Now a days, FDI has become an instrument of internationaleconomic integration.